Proceedings ILASS–Europe 2017. 28th Conference on Liquid Atomization and Spray Systems 2017
DOI: 10.4995/ilass2017.2017.4709
|View full text |Cite
|
Sign up to set email alerts
|

Spray/wall interaction analysis on an ECN single-hole injector at diesel-like conditions through Schlieren visualization.

Abstract: To continuously improve CFD models which simulate spray evolution, breakup and evaporation mechanisms, it is helpful to validate them with results obtained by experimental research. In the present study, a mono-orifice target nozzle from Engine Combustion Network, referred to as Spray D, was investigated at conditions of spray-wall interaction, which actually is a real situation in internal combustion engines that is not frequently analyzed by visualization. A Photron SA-X2 high-speed camera was employed to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…• R-parameter for penetration and spreading (R S and R Y ): In accordance with several models from spray theory [44,45], under the assumption of a cone-shaped spray, at the steady part of its evolution it can be considered that penetration is proportional to the time rised to the power of 0.5, which makes its derivative respect to the square root of time to be a nearly constant value, as shown in the sample of Figure 7, where both penetration (le ) and its derivative respect to the square root of time (right) are shown for a di erent ECN injector [35]. is constant parameter to study penetration has shown to be particularly useful since it can be analyzed regardless of the considered temporal reference [35,3,6]. : Sample of spray penetration and its R-parameter at free-jet non-reactive conditions for an ECN Spray C injector (plot adapted from [35]).…”
Section: Contour Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…• R-parameter for penetration and spreading (R S and R Y ): In accordance with several models from spray theory [44,45], under the assumption of a cone-shaped spray, at the steady part of its evolution it can be considered that penetration is proportional to the time rised to the power of 0.5, which makes its derivative respect to the square root of time to be a nearly constant value, as shown in the sample of Figure 7, where both penetration (le ) and its derivative respect to the square root of time (right) are shown for a di erent ECN injector [35]. is constant parameter to study penetration has shown to be particularly useful since it can be analyzed regardless of the considered temporal reference [35,3,6]. : Sample of spray penetration and its R-parameter at free-jet non-reactive conditions for an ECN Spray C injector (plot adapted from [35]).…”
Section: Contour Analysismentioning
confidence: 99%
“…On the one hand, the jet-wall interaction may improve the air-fuel mixing, by generating secondary atomization and enhancing the gas entrainment into the spray. Nevertheless, a fuel lm can be formed on the walls a er the impingement, rising the formation of soot and unburned hydrocarbons, besides a reduction of the engine e ciency produced by a worsening in the combustion and the heat transfer from the reactive spray to the walls [4][5][6]. Related to the wall Some experimental researches have been proposed to characterize the spray-wall interaction phenomenon, being possible to divide them into two main categories similar to what is stated by several authors [7,8]: e study of the impact of single drops, and the analysis of wall impingement of sprays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e ambient gas, initially stored in reservoirs from a compressor, is introduced into the test rig through a 30 kW electric heaters system that is in the bo om of the vessel in order to control ambient gas temperature. A er the gas is exhausted from the chamber, it is cooled down and recirculated to the compressor again or thrown to the atmosphere depending on the desired concentration of oxygen [27,25]. In this experiment, the air is introduced from the atmosphere in an open loop con guration in order to have a standard air oxygen concentration around 21%.…”
Section: Hardware 211 Visualization Test Rigmentioning
confidence: 99%
“…Consequently, the effectiveness of the post injection on reducing soot emissions is closely linked to a restrained engine bowl-shaped combustion chamber. As a matter of fact, Payri et al [41] and Zhao et al [42] concluded that spray-wall interactions enhance soot oxidation due to higher mixing with ambient air caused by wall impingement. Further, they found that the heat exchanged with the walls cooled down the jet, slowing the rate of soot formation.…”
Section: Effect Of Boundary Conditions In Soot Distributionmentioning
confidence: 99%